Identificación de Candidatus Phytoplasma asteris asociado a la enfermedad elefantiasis en el cultivo de plátano y banano en Colombia - Aliaga Valverde, Flavio Martín (2018)
Banana (Musa acuminata Group AAA) and plantain (Musa balbisiana Group AAB) are an important food sources to families and farmers dedicated to their production in the tropics and subtropics, vital to quality of life and the agricultural economy of the region. Banana Elephantiasis Disease (BED) has unknown etiology, but has been reported in Latin American countries where it causes many economic losses. BED is currently an emerging disease, which limits the crop development and reduces the production of theirs bunches. BED affect the cultivars of Gros Michel (AAA) and Dominico Harton (AAB) municipalitie of Ulloa and Alcalá, Department of Valle del Cauca and Quindío in Colombia; Seda (Group AAA), Platano Largo (Group AAB), William (Group AAA), Morado (Group AAA), Isla (Group AAB) and Palillo (Group AAB) districts of San Luis de Shuaro and Pichanaki, Department of Junín in Peru. BED causes an overgrowth from inside to outside of the pseudostem generating longitudinal and transverse ruptures of the leaf sheaths. The fruit size is reduced, the petioles reduces their insertion angles and remain rigid with a bunchy appearance; and finally, the dark brown rhizome develops conically with bud proliferation and the ruptures of the leaf sheaths lead to the collapse of the whole plant. The random distribution of the disease observed in the field suggests the possible participation of insect vectors, secondary hosts and the use of infected planting material. According to a survey conducted during 2016 and 2017, this disease reduces the yields of Gros Michel (Group AAA) and Dominico Hartón (Group AAB) anywhere from 9% to 71.6% in the municipalities of Ulloa and Alcala in the department of Valle del Cauca in Colombia. Total DNA was extracted with CTAB extraction protocol from symptomatic and asymptomatic plants. Conventional PCR used primers that amplify the phytoplasma 16S ribosomal RNA gene, P1/Tint followed by primers fU5/rU3 in a nested PCR reaction. The fTuf1/rTuf1, fTufu/rTufu and Tuf400/Tuf835 primer were used to amplify the phytoplasma EF-Tu (tuf) parcial gene. Plants grown in vitro were used as negative controls and positive controls were synthetic DNA of Candidatus Phytoplasma 16SrIII. All samples were evaluated by Real Time ? PCR with universal phytoplasma probe. To confirm that the observed symptoms were associated with phytoplasma, one sample of rhizome from symptomatic and asymptomatic plant was selected for each farm to amplify the V4 region of the 16S gene with the 515F/806R primers in the HiSeq Illumina platform. BLAST analysis of DNA sequences of 16S rRNA gene (MF629790, MF662673) from rhizome tissues of symptomatic banana, showed 99% sequence identity with Candidatus Phytoplasma asteris, phylogenetic analysis showed 99% of similarity with the 16SrI?S subgroup and RFLP analysis in silico with MseI, AluI and RsaI endonucleases showed fragment profiles that belong to the phytoplasma 16SrI group (?Aster Yellows?). Phylogenetic analysis of DNA sequences of EF?Tu (tuf) gene were associated as an independent group and at the same time showed 98% of similarity with the phytoplasma 16SrI and 16SrXII group. 12 OTUs of Candidatus Phytoplasma were found only in symptomatic plants. BLAST analysis showed a 99% sequence identity (MF977376-MF977387) with Candidatus Phytoplasma. This research demonstrates for the first time in the world that Candidatus Phytoplasma is an organism associated with Banana Elephantiasis Disease (BED) in Colombia.